State of research and research possibilities of early medieval pottery from the Prague production zone - Boháčová, Ivana (Institute of Archaeology and Ethnology Polish Academy of Sciences, 2017)
The current aim of the study of pottery from the Prague production zone is a detailed understanding of the changes in the pottery in connection with chronology and an explanation of the essence and causes of these changes while also capturing similarities and differences within the studied region. Accomplishing these goals will require a detailed evaluation of a larger number of pottery collections from key stratified contexts, i.e., from specific, chronologically well-defined contexts which were, for example, unaffected by post depositional processes, created in clearly demarcated intervals or allowing an absolute chronology to be established for the events that they document. A comparative online database of pottery from the Prague production zone created for this purpose should speed up the flow of information on key reference collections from the studied area
il. ; 24 cm
Keywords: średniowiecze wczesne; archeologia; ceramika; Praga; chronologia